1999
DOI: 10.1002/(sici)1520-6807(199907)36:4<327::aid-pits6>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Students with emotional/behavioral disorders and transition planning: What the follow‐up studies tell us

Abstract: This paper will examine the current literature and implications of follow-up studies of students with emotional/behavioral disorders (EBD) focusing on the postschool outcomes of this population. The examination of the follow-up studies gave a perspective of transition and postschool outcomes for youths with EBD. In our research, we found 22 follow-up studies that examined the EBD population as a subset of a larger pool of youths with disabilities, yet found only eight studies that examined the EBD population e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The in-and postschool outcomes of adolescents with ED-outcomes that generally are worse than for any other disability category-serve as indicators that students may exhibit substantial skill deficits in the area of self-determination (e.g., Wagner, Cameto, & Newman, 2003;Wood & Cronin, 1999). However, clear descriptive data addressing the selfdetermination of adolescents with ED remain absent from the literature.…”
mentioning
confidence: 99%
“…The in-and postschool outcomes of adolescents with ED-outcomes that generally are worse than for any other disability category-serve as indicators that students may exhibit substantial skill deficits in the area of self-determination (e.g., Wagner, Cameto, & Newman, 2003;Wood & Cronin, 1999). However, clear descriptive data addressing the selfdetermination of adolescents with ED remain absent from the literature.…”
mentioning
confidence: 99%
“…Students who exhibit emotional and/or behavioural difficulties (E/BD) are at-risk for poor academic and psychosocial outcomes (e.g. Wood & Cronin, 1999). Recent large-scale data from the United States (Wagner, Kutash, Duchnowski, Epstein, & Sumi, 2005) and Canada (Whitley, Lupart, & Beran, 2009) highlight the social and academic difficulties experienced by elementary and secondary-aged students with school-identified E/BD.…”
Section: Future Researchmentioning
confidence: 99%
“…Recent large-scale data from the United States (Wagner, Kutash, Duchnowski, Epstein, & Sumi, 2005) and Canada (Whitley, Lupart, & Beran, 2009) highlight the social and academic difficulties experienced by elementary and secondary-aged students with school-identified E/BD. In fact, according to some researchers, students with E/BD experience less school success than any other group of students, whether identified with an exceptionality or not (Landrum, Tankersley, & Kauffman, 2003;Wagner et al, 2005;Wood & Cronin, 1999). Within the Canadian education system, students with E/BD may be formally identified for special education services through a combination of teacher observation and referral, parent observation, and psychological assessment (Visser, Daniels, & Cole, 2001;Zionts, Zionts & Simpson, 2002).…”
Section: Future Researchmentioning
confidence: 99%
“…There have been several follow‐up studies of young people identified as having emotional and behavioural difficulties, mainly conducted in either the UK (for example, Farrell & Polat, 2003) or the USA (for example, Blackorby & Wagner, 1996). There has also been one published review of this literature (Wood & Cronin, 1999). After an investigation of the research on this topic, it was found that only four studies have focused on the views of students with emotional and behavioural difficulties about their experiences of residential schools (Cooper, 1993; Jahnukainen, 2001; Polat & Farrell, 2002; Smith, Meltonay & Chakrabarti, 2004).…”
Section: Introductionmentioning
confidence: 99%